2012
DOI: 10.1155/2012/530721
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Thyrotropin Serum Concentrations Gradually Increase from Benign Thyroid Nodules to Papillary Thyroid Microcarcinomas Then to Papillary Thyroid Cancers of Larger Size

Abstract: We evaluated the preoperative serum thyrotropin (TSH) levels in 386 patients operated on for nodular thyroid disease (NTD). TSH levels for cases with final benign disease and differentiated thyroid carcinoma (DTC) were compared. No evidence of cancer was detected in 310 patients (80.3%), whereas malignancy was present in 76 cases (19.7%). Mean TSH concentration was 1.36 ± 1.62 mU/L in benign patients and 2.08 ± 2.1 in cases with malignant lesions (P = 0.0013). The group of malignancy was subdivided in papillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
27
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 17 publications
7
27
1
Order By: Relevance
“…In contrast to the report by Liu et al [6], there was no significant correlation between NLR and TSH in our cases. TSH is a growth factor and promotes the carcinogenesis of PTC [18]. In support of this, TSH signaling enhanced the transformation of mice with a thyroid-specific knock-in of oncogenic Braf (LSL-Braf V600E/TPO-Cre) [19].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the report by Liu et al [6], there was no significant correlation between NLR and TSH in our cases. TSH is a growth factor and promotes the carcinogenesis of PTC [18]. In support of this, TSH signaling enhanced the transformation of mice with a thyroid-specific knock-in of oncogenic Braf (LSL-Braf V600E/TPO-Cre) [19].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in patients with nodular thyroid disease, L-thyroxine (L-T4) treatment, reducing serum TSH, is associated to a significantly lower risk of developing clinically detected thyroid cancer (28). The relationship between serum TSH and microPTC is not clear-results reported in the literature being discrepant and relying only on retrospective studies (29,30,31,32,33,34,35).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that the risk of thyroid malignancy was associated with some thyroid functional parameters, such as serum thyroid stimulating hormone (TSH) level [7]. However, there have been conflicting results regarding the roles of these thyroid functional parameters [8].…”
Section: Introductionmentioning
confidence: 99%